Genetic diversity and relationships between some agronomic traits of chickpea genotypes (Cicer arietinum L.) under non-stress and terminal drought stress conditions - Maryam Rezaeinia; Mohammad Reza Bihamta; Seyed Ali Peyghambari; Alireza Abbasi; Fatemeh Gharajedaghi (پژوهش‌های حبوبات ایران)
Introduction Legumes are one of the most important sources of protein in the diet of many people in developing countries and are the second largest source of human food. Chickpea (Cicer arietinum L.) ranks 2nd in cultivated area of legumes in the world. Low chickpea performance in Iran with respect to environmental conditions and inaccessibility to adequate water and appropriate genotype and little breeding works has been done on it. Since the main components of genetic and environmental factors that determine the yield and quality of plants, the main purpose of the selection of breeding indices, should focus more on the effects of genetic factors. Genetic diversity in chick pea collection can be used in breeding program for selection of genotype with desirable agronomic traits. Studying relationships between agronomic traits would assist breeders to identify the effective traits and use proper selection intensity in their breeding programs.